Uji Validitas Konstruk Indonesian-Psychological Measurement of Islamic Religiousness (I-PMIR) - Diana Fitria Salsabila; Rifa Rofifah; Yonathan Natanael; Zulmi Ramdani (Jurnal Psikologi Islam dan Budaya, 2019)
This study aims to test the validity of the construct of the Indonesian version of Islamic religiosity measuring instrument called the Indonesian-Psychological Measurement of Islamic Religiousness (I-PMIR) developed by the researchers. This study used quantitative methods with 57 items I-PMIR to verify five dimensions in Islamic religiosity. Research participants were 591 Muslims in Indonesia. Based on the results of the Confirmatory Factor Analysis (CFA) using MPlus software, it was found that there were 52 valid items measuring Islamic religiosity. This scale is suitable to be used as an appropriate instrument to explore individual religiosity in an Islamic context.